Sociomateriality and the metaphysics of accounting information systems: Revisiting agential realism - Vosselman, Ed; De Loo, Ivo (International journal of accounting information systems, 2023)
•In a representationalist understanding an AIS provides (imperfect) representations serving human intervention.•In an agential realist understanding an AIS is performative.•Representationalism provides a humanist understanding, while agential realism offers a posthumanist understanding of AIS.•Agential realism discloses how accounting information systems participate in the (re)configuring of a sociomaterial world.•Agential realism in AIS-research can complement, not substitute, representationalism in AIS-research. This paper is a response to Weber’s (2020) call for further debate on the (potential) contribution of agential realism for the understanding of the content and functioning of accounting information systems (AIS) (Weber, 2020). Contrary to Weber’s conclusions, we suggest that agential realism can make important contributions to AIS studies. In order to realize such contributions we have to acknowledge that agential realism is a metaphysical framework rather than a theory or epistemology. Its potential contributions should be set against the potential contributions stemming from the metaphysical framework that is dominant in AIS research: representationalism. In representationalism, for the purpose of creating a knowledge base for a distant ‘knower’ who acts on the basis of such knowledge, accounting information systems are assumed to represent or provide information about a reality that is ‘out there’. In agential realism, accounting is assumed to be performative in (re)configuring local and temporal boundaries between meaningful positions for humans and non-humans. Rather than putting the human subject (the knower) at the centre of the stage, an agential realist account of accounting foregrounds accounting practices in their interrelation with other practices. It acknowledges that accounting participates in the (re)configuring of a sociomaterial world.